"Ancient" protocols for the crime scene? Similarities and differences between forensic genetics and ancient DNA analysis. - Capelli, C; Tschentscher, F; Pascali, V (2003)
We provide a short overview on some current issues in the fields of forensic genetics and ancient DNA (aDNA) analysis. We discuss about the existence of the possible points of contact between the two disciplines, in terms of open problems and the inherent approach to their solution. We mainly focus on the problem of results authentication, its theoretical and technical aspects.